Reversible Changes of Brain Perfusion SPECT for Carbon Monoxide Poisoning-Induced Severe Akinetic Mutism - Chen, Shao-Yuan; Lin, Chun-Chieh; Lin, Yi-Te; Lo, Chung-Ping; Wang, Chen-Hsu; Fan, Yu-Ming (Clinical nuclear medicine, 2016)
This study aimed to characterize changes in regional cerebral blood flow (rCBF) in patients who experienced carbon monoxide (CO) poisoning and subsequently developed severe delayed neuropsychiatric sequelae (DNS) with akinetic mutism. We determined whether these changes were reversible in parallel with improvements in neuropsychological function in response to treatment, including hyperbaric oxygen therapy. Patients who developed severe DNS with akinetic mutism after acute CO intoxication between 2007 and 2011 were enrolled. Tc-ECD brain SPECT findings were compared between the patients with severe akinetic mutism and age-matched control subjects to characterize the pattern of rCBF. Perfusion SPECT was correlated with clinical outcomes after treatment with statistical parametric mapping (SPM8); the height threshold was P < 0.01 at peak level, and the corrected false discovery rate was P < 0.05 at the cluster level. Seven patients with akinetic mutism were analyzed. All patients had neurological symptoms caused by acute CO exposure, and all recovered to nearly normal daily function after initial treatments. In all cases, after a "lucid interval," DNS progressed to akinetic mutism. The SPECT images acquired at the onset of akinetic mutism demonstrated variable hypoperfusion in frontal-temporal-parietal regions, with the greatest severity in the left temporal-parietal regions. In parallel, we performed functional neuropsychiatric tests. After treatment, the brain SPECT showed significantly fewer hypoperfusion regions, and neuropsychiatric tests showed dramatically improved function. Our findings demonstrated both cerebral cortical and subcortical injuries in patients with CO-induced akinetic mutism. Improvement in rCBF correlated well with functional recovery after treatment.